Alpha-synuclein fibrils induce budding of mitochondrial-derived vesicles - Thomas Braun; Viviane Reber; Cinzia Tiberi; Andri Fränkl; Dhiman Ghosh; Roland Riek; Tetiana Serdiuk (Proceedings of the National Academy of Sciences, 2026)
α-synuclein (α-syn) aggregation is a hallmark of synucleinopathies, a class of neurodegenerative disorders such as Parkinson’s disease (PD). Several lines of evidence indicate the involvement of mitochondria in the disease pathology. Despite extensive study, the link between α-syn aggregation and mechanisms of mitochondrial toxicity remains not fully understood. Using high-resolution imaging with electron microscopy, we examined SH-SY5Y cells exposed to α-syn fibrils vs control cells with a focus on mitochondria. We found that upon exposure to α-syn fibrils, mitochondria cristae structure gets defects, and mitochondria enhance the budding of mitochondrial-derived vesicles (MDVs). MDV formation reflects an evolutionarily conserved mechanism reminiscent of bacterial outer membrane vesicle biogenesis. Structural proteomics analysis by mass spectrometry corroborates this microscopy observation by identifying changes in multiple proteins that regulate cristae structure, MDV formation, and trafficking. Our results suggest that α-syn may promote MDV generation, and support an important link between α-syn and mitochondria which will be important for future mechanistic studies. The processes we detected could be of interest for diagnostics and potential therapeutic interventions.